Gambaran Kualitas Tidur Penderita Hipertensi di Puskesmas II Denpasar Barat - Bunganing Eswarya; I Gede Bagus Gita Pranata Putra; I Ketut Tangking Widarsa (Aesculapius Medical Journal, 2023)
Hypertension is a condition in which the blood pressure is above 140/90 mmHg. Hypertension could be prevented by controlling the sleep quality. Until now there has not been any studies to clearly depict sleep quality. This study aims to understand the description of sleep quality as well as its characteristic in Puskesmas II Denpasar Barat hypertension subjects. Observational descriptive study was used using cross sectional method and consecutive sampling. The study conducted at Puskesmas II Denpasar Barat with 96 total samples. Pittsburg Sleep Quality Index (PSQI) questionnaire was used to assess the quality of sleeps. Data gained from the questionnaire was analyzed bivariately and univariately. The results shows that more than a half (64%) hypertension patients are having a poor sleep quality with long sleep latency as the component with the highest proportion (57,3%). Poor sleep qualities are more frequent in patients within the age range of 18-39 years rather than older patients. This study also finds that higher hypertension grade appears more often as the sleep quality gets worse. With this study, hopefully Puskesmas II Denpasar Barat could emphasize the importance of sleep quality as a preventive act towards fighting hypertension. Keywords: Hypertension, Quality of Sleep